Pengaruh Disiplin Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Semua Operator - Puspita Sari, Riska Dwi; Sukaris, Sukaris (Universitas Muhammadiyah Gresik, 2024)
Background – The phenomenon that exists in PT. Semua Operator have low work discipline in employees, this can be seen from the level of employee tardiness. In addition, employees are also indicated to have problems that arise that arise from less harmonious relationships between employees caused by different work locations, and the existence of a schedule for changing hours for these work locations. Objective – This study aims to determine the influence of discipline and work environment on employee performance at PT Semua Operator. Design / Methodology / Approach – The population in this study is employees of PT All Operators totaling 65 respondents. This study uses a type of quantitative research, sampling techniques using saturated sampling techniques. The sample used was 65 employees of PT Semua Operator. Findings – The results of this study show that discipline has an effect on employee performance and the work environment variable has no effect on employee performance. Research Implication – Relationships between employees that are less harmonious and employee work discipline are still low can cause employee performance to be not optimal and even. Limitations – This research was only conducted on employees of PT. Semua Operators So that the ones who determine the respondents to be used are employees who work at PT. Semua Operators.